Interactive Holograms and Tutorials in Healthcare Education: Case Studies from the e-REAL Experience - Salvetti, Fernando; Bertagni, Barbara (International Journal of Advanced Corporate Learning (iJAC), 2016)
With both portable and permanent fixtures available, the e-REAL lab encompasses users in an entirely interactive and immersive ecosystem; advanced medical simulation reaches its best thanks to interactive 3D holographic visualization. Using a number of tools, e-REAL enables not only face-to-face training, but also e-learning and remote communication across the globe.